PLAN DE MARKETING PARA LA COMERCIALIZADORA”VIVANCO COBOS VICOSA” CIA. LTDA, EN LA CIUDAD DE LOJA EN EL PERIODO 2015 - 2016 - Cevallos Marquez, Italo Ivan (2016)
The Marketing Plan identifies the environment in which the company operates and thus, to take the necessary decisions to ensure normal operation and this supports the company more competitive and can generate a better position in the market which develops. The overall objective for the development of this thesis is to make a marketing plan for VIVANCO COMERCIALIZADORA COBOS VICOSA CIA. LTDA, knowing that a marketing plan within the company constitutes a basic factor, as the customer needs detected through policies that seek to meet those needs and meet them at the same time allows develop strategies to provide for the development of the organization. Thus the development of this work objectives for the development of the marketing plan for marketing VICOSA thereof which are raised;  Conduct an external economic, social and cultural, ecological, technological and demographic policy analysis variables affecting the company  Conduct a competitive analysis  Conduct an internal analysis  Make a market study  To design a proposal for a marketing plan for marketing VIVANCO VICOSA COBOS For the implementation of the first objective assessment of external factors was performed to determine the opportunities and threats presented in the environment of the company. Once the collection of information with key officials VICOSA trading proceeded with a sparkler opportunities and less relevant threats to then perform Assessment Matrix External Factors (Opportunities - Threats) that influence the business life the VICOSA, the same trader who was the subject of the evaluation matrix rating of external factors has 17 determinants of success including 8 9 opportunities and threats. The result obtained is 2.87 this result is equivalent is located above the standard value is 2.50 indicating that the company is stable and is taking advantage of the opportunities offered by the environment. 7 For the second objective first research the commercial sector was carried out as it is, what are its advantages, disadvantages, determining that the commercial sector is the main economic activity of major importance Ecuador, wholesale and retail has a representing 54% nationally. Showing that slightly more than half of the companies engaged in trade in Ecuador according to the INEC, then the analysis of the 5 forces PORTER was performed according to the company environment VICOSA the same who contributed to the research as they are : THREAT of ENTRY oF COMPETITORS, companies are starting their activities just as the trading among which are; DARPA, TONI, V & M, Shopping Servicie that would be indirect competitors have the direct competitors; CAMEL, BALD & BALD, ROMAR, FAGI products or companies that can replace the activities of the company are SUPERMAXI, TIA, Micro markets, among others. BARGAINING POWER WITH client.- are the strategies of the company to attract and retain customers in which we can highlight the search for new suppliers to attract new customers with other buying preferences and penetrate other markets, POWER NEGOTIATING wITH sUPPLIERS, for which a list of suppliers that the company has what are the advantages and disadvantages that have over other providers among which are performed; Jaboneria WILSON, CONFITECA, INGENSA, BIG, MARCESAL.S.A, ELITE PAPER (TISSUE PRODUCTS), ACKERLANDSEEDS (Canada). Then the matrix of competitive profile was developed taking into account the direct competitors that the company, allowing determine how the company is facing competitors, the array has 10 key success factors is an adequate number of factors where we can observe the values of trading VICOSA it is slightly above 3.18 worth more than the marketing & BALD BALD thereof having a value of 3.08 while other distributors are below the level of the marketer. For the third objective internal analysis with the direct collaboration of key personnel manager company, sales manager, accountant who gave me the information relevant to the realization of the Evaluation Matrix Internal Factors (Strengths - Weaknesses) it was held in where their weights and grades are based on the study and analysis of this marketing plan; the matrix has a component of 13 determinants of success in July strengths and weaknesses in 8 June, an adequate number of factors, but with subjective 0.08 and 0.06 pesos as the weighted result of 2.85 was obtained is the same as above standard value is 2.50, it is considered that the organization is balanced. For the fourth objective a sample size of customers that the company is 2,549 giving a total of 334 clients was conducted. Surveys customers of the trading were silver, after investigating variables to collect the necessary information for research Marketing Plan, 39% of respondents are loyal to the marketer for more than six years. 40% of surveyed customers have a pre-emption by the line of toiletries and cleaning while 45% of customers acquire the fortnightly products mind, 61% of customers said that the prices are equal to those of the competition, 96% tells us that the only advertising or means learning the different products that have the marketing are selling agents, 29% of customers stated that acquires products VICOSA by the great variety of them, while 74% of customers knew stating that the product has an acceptable quality and 88% received promotions to sometimes more products purchased. Subsequently these analyzes a proposal that would constitute the fifth objective where a company presentation, mission, vision ,, values with which to work the business to achieve the vision, policies that should govern detailed was developed within the company and its workers, the opportunity for growth that the company has the environment in which performs presents a congruence of opportunities the same as reflected in the era of technology innovation in the country thus allowing easy access to new and best technologies that will enable the company to develop whether these software programs, computer equipment machinery, strategies using the SWOT matrix, the competitive participation of the company to the products it offers over other traders, a strategic map which will serve as a guide to achieve certain strategic objectives and what objectives will be operating or strategies to achieve them.